REGARDING A METHOD OF PERFORMING ON THE VIOLIN IN TRADITIONAL MUSIC - MIRONENCO, IAROSLAV (Notograf Prim, 2018)
Following a field study in the village of Lozova, Străşeni, aimed at identifying the variants of a folk song recorded by I. Mironenko from an informant living in the village of Thamaha, North Caucasus — Russia, a village inhabited by Moldovans, the musicologist discovered a fiddler who demonstrated him a specific process of executation on the violin. This method is representative of an advanced level of interpretation on the violin.